Dimensions of poverty and inconsistent condom use among youth in urban Kenya - Davidoff-Gore, Alena (2011)
To date, research on the link between poverty and unsafe sexual behaviors has utilized limited measures of socioeconomic status and has overlooked key dimensions of poverty at the individual level. This study explored how various dimensions of socioeconomic status are associated with inconsistent condom use and how these associations vary by gender. We analyzed unique life history survey data from 261 young men and women in Kisumu, Kenya, and conducted analyses based on 959 person-months in which respondents had been sexually active in nonmarital relationships. Dependent variables were inconsistent condom use (not always using a condom) and never use of condoms. Condoms were used inconsistently in 57% of months and were never used in 31%. Corroborating existing literature, lower household wealth and lower educational attainment were associated with inconsistent condom use. Lower individual economic status (lower earned income, food insufficiency, and larger material transfers from partners) were also important determinants of inconsistent condom use. There were no significant differences in these associations by gender, with the exception of food insufficiency, which increased the risk of inconsistent condom use for young women but not for young men. None of these individual measures of socioeconomic status were associated with never use of a condom. The findings suggest that both household- and individual-level measures of socioeconomic status are important correlates of condom use and that individual economic resources play a crucial role in negotiations over the highest level of usage. The results highlight the importance of poverty in shaping sexual behavior, and, in particular, that increasing individual access to resources beyond the household, including ensuring access to food and providing educational and work opportunities, could prove to be effective strategies for decreasing the risk of HIV among youth.